Online Businesses Tax Morale in Supply Chain Relationships - M. Mansor; I. Ibrahim; N. Mat Udin; N. Saad (International Journal of Supply Chain Management, 2019)
The number of e-commerce (online) businesses is increasing in Malaysia, providing opportunities for digital business platforms to generate billions of ringgit in revenue. However, the businesses do not pay tax due to the absence of an efficient tax structure for this kind of supply chain management. The government will be looking at ways to tax individuals engaged in e-commerce (online) businesses to address its lost opportunity for revenue from a fast-growing segment of the economy. In addition, clearer guidelines are needed when there is a mixed supply chain operating within a holding company structure when it involves online business transactions. To combat such tax non-compliance by online businesses, it is essential to understand the levels of tax morale of these online businesses. Therefore, the purpose of this study was to unveil the level of tax morale of online businesses and to generate a tax morale framework for online businesses. Using a qualitative research methodology, the result of this study found four major levels of tax morale that are ‘input’, ‘process’, ‘output’ and ‘outcome’. The ‘input’ level consists of tax knowledge, tax obligations and self-awareness. The ‘process’ level consists of the necessity to follow the business law and tax law, as well as the tax enforcement implemented by the tax authority. The ‘output’ level consists of the online business owners’ trust towards the tax authority and government. Efficient correlation among the ‘input’, ‘process’ and ‘output’ levels of their tax morale will provide an effective ‘outcome’ in terms of voluntary tax payment to the tax authority that will bring benefit to the community in general. Based on the results obtained regarding the levels of tax morale of the online businesses, this research has developed the tax morale framework for online businesses.